Analysis of the Use of Palm Shells as a Substitute for Fine Aggregate on the Water Absorption of Concrete - Iswady, Iswady; Gusty, Sri; Chaerul, Muhammad (ASTONJADRO, 2025)
Concrete, as one of the main elements in construction, has received special attention and is commonly used in infrastructure development in various countries in the world. High-quality concrete is increasingly needed along with the increasing need for infrastructure, such as towers, high-rise buildings, and long-span bridges. This type of concrete is made with a low amount of FAS; FAS or water-to-cementitious ratio is the ratio of the total weight of water to the total weight of cement in the concrete mixture. The purpose of this study is to analyze the water absorption of concrete using palm shells as a substitute for fine aggregate using an experimental method by curing. From the results of testing palm shells such as the water absorption value which is directly proportional to the increasing percentage of CKS use as a substitute for fine aggregate, it show that the use of CKS as a substitute for fine aggregate in normal concrete increases the water absorption of concrete, the higher the percentage of palm shell substitution, the higher the percentage of absorption value obtained.